2005
DOI: 10.1554/05-211.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Costs of Mosquito Resistance to Malaria Parasites

Abstract: Costly resistance mechanisms have been cited as an explanation for the widespread occurrence of parasitic infections, yet few studies have examined these costs in detail. A malaria-mosquito model has been used to test this concept by making a comparison of the fitness of highly susceptible lines of mosquitoes with lines that are resistant to infection. Malaria infection is known to cause a decrease in fecundity and fertility of mosquitoes; resistant mosquitoes were thus predicted to be fitter than susceptible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 59 publications
(83 reference statements)
1
71
2
1
Order By: Relevance
“…These findings offer an interesting contrast to the results of Hurd and colleagues (11,12) who reported that the parasite imposes a fitness cost on the mosquito (as we found) but that resistant mosquitoes that up-regulate natural immune responses to Plasmodium infection are not more fit than nonresistant mosquitoes, presumably because the fitness costs of being hyperimmune negate the fitness advantage of not being infected. A potential explanation for this discrepancy is that the transgenic mosquitoes used in our study are Plasmodium-refractory because of expression of a presumably harmless (2) gene (SM1) rather than activation of the endogenous innate immune cascade.…”
Section: Resultscontrasting
confidence: 99%
“…These findings offer an interesting contrast to the results of Hurd and colleagues (11,12) who reported that the parasite imposes a fitness cost on the mosquito (as we found) but that resistant mosquitoes that up-regulate natural immune responses to Plasmodium infection are not more fit than nonresistant mosquitoes, presumably because the fitness costs of being hyperimmune negate the fitness advantage of not being infected. A potential explanation for this discrepancy is that the transgenic mosquitoes used in our study are Plasmodium-refractory because of expression of a presumably harmless (2) gene (SM1) rather than activation of the endogenous innate immune cascade.…”
Section: Resultscontrasting
confidence: 99%
“…The hatching success in our study was similar to other lab colonies of A. gambiae [43 – 63%; [40]], but lower than that of field-collected individuals [86%; [39]], suggesting some inbreeding effects. In mosquitoes of the genus Culex and Aedes , low hatching success is commonly caused by Wolbachia , a maternally inherited bacteria that induces cytoplasmic incompatibility where sperm from infected males are unable to fertilize the eggs of uninfected females, however, this phenomenon is not known to occur in Anopheline mosquitoes [41].…”
Section: Discussionsupporting
confidence: 85%
“…The genetic architecture of female fitness and malaria resistance has understandably been the focus of much theoretical [42,43] and empirical work [40,44] given its epidemiological significance. However, as molecular biologists reveal the abundance of genes involved in protecting female mosquitoes from malaria parasites [45-48] and as others, using a variety of insects, demonstrate the ubiquity of trade-offs between immunity and other life history traits [49-51], there is a growing awareness that unless the expression of these anti-malarial genes is perfectly sex-linked, males will play a role in their evolution.…”
Section: Discussionmentioning
confidence: 99%
“…For example, how are parasites able to develop and escape from the mosquito immune response? Given that the lifespan of the mosquito is not much longer than 30 days (Grieco et al, 2003; Hurd et al, 2005), and that parasite development takes, depending on the species of Plasmodium , from 15 to 25 days, how is it possible that the mosquito can transmit the parasite to humans? Moreover, what is the nature of the signals that activate the immune response against this parasite and associated damage?…”
Section: Introductionmentioning
confidence: 99%